THE POPULARIZATION OF THE ENGLISH LANGUAGE AMONG YOUTH AND THE PRESIDENT`S RECENT ATTENTION TO TEACHERS (American Journal of Pedagogical and Educational Research, 2025)
Ensuring the quality of teaching foreign languages to the growing young generation, radically improving the system of training specialists who can speak foreign languages fluently, and preparing qualified personnel who meet international educational standards are among the main goals of the educational reforms carried out in our country.